Bioprospection of immature salivary glands of Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae). (September 2018) - Caleffe, Ronaldo Roberto Tait; de Oliveira, Stefany Rodrigues; Gigliolli, Adriana Aparecida Sinópolis; Ruvolo-Takasusuki, Maria Claudia Colla; Conte, Helio
Highlights: Immature salivary glands of C. megacephala are described at morphological and ultrastructural levels. Cells of salivary glands present intense protein synthesis. The molecular weight of soluble proteins of salivary glands were described. Abstract: Larval therapy (LT) comprises the application of sterile Calliphoridae larvae for wound debridement, disinfection, and healing in humans and animals. Larval digestion plays a key role in LT, where the salivary glands and gut produce and secrete proteolytic and antimicrobial substances. The objective of this work was to bioprospect the salivary glands of Chrysomya megacephala (Fabricius, 1794) larvae, using ultrastructural, morphological, and histological observations, and the total protein electrophoretic profile. The salivary glands present a deferent duct, originating from the buccal cavity, which bifurcates into efferent ducts that insert through a slight dilatation to a pair of tubular-shaped tissues, united in the region of fat cells. Histologically, the secretion had protein characteristics. Cell cytoplasm presented numerous free ribosomes, autophagic vacuoles, spherical and elongated mitochondria, atypical Golgi complexes, and dilated rough endoplasmic reticulum. In the apical cytoplasm, secretory granules and microvilli secretions demonstrated intense protein synthesis, basal cytoplasm with trachea insertions, and numerous mitochondria. The present work described the ultrastructure and morphology of C. megacephala third instar salivary glands, confirming intense protein synthesis and the molecular weight of soluble proteins.